1998
DOI: 10.1002/(sici)1097-0290(19980320)57:6<642::aid-bit2>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and rate laws of growth and death of hybridoma cells in continuous culture

Abstract: Experimental data from six hybridoma cell lines grown under diverse experimental conditions in both normal continuous and perfusion cultures are analyzed with respect to the significance of nutrients and products in determining the growth and death rates of cells and with respect to their mathematical modeling. It is shown that neither nutrients (glucose and glutamine) nor the common products lactic acid, ammonia, and monoclonal antibody can be generally assumed to be the clear‐limiting or inhibiting factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 29 publications
1
50
0
1
Order By: Relevance
“…Long lag phases are undesirable, therefore high growth rates are essential at the beginning of a process to achieve sufficient cells for maximal production. Uncontrolled proliferation beyond a certain desired cell density is also undesirable due to nutrient and oxygen depletion, toxic metabolite accumulation, cell death, and degradation of the products (Al-Rubeai and Singh 1998;Zeng et al 1998, Zeng andDeckwer 1999). Proliferation control strategies are typically implemented in the mid-or late-phases of exponential growth and have been shown to improve both the productivity and duration of production processes.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Long lag phases are undesirable, therefore high growth rates are essential at the beginning of a process to achieve sufficient cells for maximal production. Uncontrolled proliferation beyond a certain desired cell density is also undesirable due to nutrient and oxygen depletion, toxic metabolite accumulation, cell death, and degradation of the products (Al-Rubeai and Singh 1998;Zeng et al 1998, Zeng andDeckwer 1999). Proliferation control strategies are typically implemented in the mid-or late-phases of exponential growth and have been shown to improve both the productivity and duration of production processes.…”
Section: Introductionmentioning
confidence: 85%
“…Inefficient use (higher uptake than required for normal cell growth) of glucose and glutamine leads to rapid biomass generation, nutrient depletion and by-product accumulation (lactate and ammonium ions, etc.) which often have inhibitory effects on culture longevity and productivity (Ozturk et al 1992;Zeng et al 1998;Zeng and Deckwer 1999). Finding alternative compounds that can be used efficiently as carbon and energy sources with lower uptake rates is important because slow consumption of nutrients can lead to reduced/ arrested cell growth (Altamirano et al 2001b).…”
Section: Media Formulation Approaches For Nutrient Based Cell Prolifementioning
confidence: 99%
“…Zeng et al (1998) proposed in a comparison of six hybridoma cell lines that the specific growth rate is limited by either an auto-inhibitor or an unknown limiting growth factor, which manifests itself through the strong dependence of on the ratio of cell number to dilution rate N v /D. The growth rate correlates negatively and almost linearly for all cultures, in both chemostat and perfusion modes, with the ratio of viable cell number to the dilution (perfusion) N v /D, until cessation of growth is reached.…”
Section: Single Cell Modelsmentioning
confidence: 99%
“…The work of Lee et al (1995) proposed the dependence of specific cell death rate on a non-growth linked auto-inhibitor and suggested a positive linear correlation between K d and N v /D. Zeng et al (1998) tested this relation on a number of hybridoma cell lines and found it to hold only for some chemostat cultures and only at relatively low values of N v /D. For higher values, the relation becomes severely non-linear.…”
Section: Single Cell Modelsmentioning
confidence: 99%
See 1 more Smart Citation